1)x2-19/x+корень19 2)кореньx-6/x-36 3)m+8корень м/m-64 4)29-корень29/корень 29...

0 голосов
86 просмотров

1)x2-19/x+корень19
2)кореньx-6/x-36
3)m+8корень м/m-64
4)29-корень29/корень 29
5)11-корень33/корень33-3


Алгебра (22 баллов) | 86 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

Везде применима формула разности квадратов
                     a² - b² = (a - b)(a + b)

1)
\frac{ x^{2} -19}{x+ \sqrt{19} }= \frac{(x+ \sqrt{19})(x- \sqrt{19})}{x+ \sqrt{19} } =x- \sqrt{19} 
2)
\frac{ \sqrt{x} -6}{x-36}= \frac{ \sqrt{x} -6}{( \sqrt{x} -6)( \sqrt{x} +6)}= \frac{1}{ \sqrt{x} +6}
3)
\frac{m+8 \sqrt{m} }{m-64}= \frac{ \sqrt{m}( \sqrt{m} +8)}{( \sqrt{m} +8)( \sqrt{m}-8)}= \frac{ \sqrt{m}}{ \sqrt{m} -8} 
4) 
\frac{29- \sqrt{29} }{ \sqrt{29}}= \frac{ \sqrt{29}( \sqrt{29}-1)}{ \sqrt{29}}= \sqrt{29}-1 
5)
\frac{11- \sqrt{33} }{ \sqrt{33} -3} = \frac{(11- \sqrt{33} )( \sqrt{33} +3)}{( \sqrt{33} -3)( \sqrt{33} +3)} = \frac{11 \sqrt{33} - \sqrt{33}^{2}+33-3 \sqrt{33}}{ \sqrt{33} ^{2}-9}= \frac{8 \sqrt{33} -33+33}{33-9}= \frac{8 \sqrt{33}}{24}= \frac{ \sqrt{33} }{3}

(35.1k баллов)